Strategi Bisnis Sebagai Dasar Keunggulan Kompetitif Bagi Usaha Mikro di Kota Bandung : Peran Model Inovasi - Nabilah Zulkhairi Putri (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Micro enterprises in Indonesia are known to have obstacles in innovating, even though innovation is one of the demands in today's modern industrial era. The involvement of innovation in business strategy can be a strength for micro enterprises to grow and develop. The purpose of this study is to determine the role of innovation models in mediating the relationship between business strategy and competitive advantage in micro-enterprises in Bandung City. The method used is descriptive analysis and verification with non-probability sampling techniques. Data processing uses the PLS-SEM model through SmartPLS 4.0 with 100 micro enterprises as respondents. The research findings state that business strategy has a significant effect on competitive advantage. In addition, it is known that process and product innovation mediate the influence of business strategy on competitive advantage, but only on differentiation strategy. Meanwhile, human resource innovation has no influence as a mediator. Therefore, micro enterprises that use differentiation strategy are advised to carry out process and product innovation to increase competitive advantage. However, micro-enterprises that implement cost-leadership strategy are recommended to focus on cost efficiency strategy.